Soil data definition for hydrologic response unit (HRU) analysis in soil water assessment tool (SWT) model of Langkawi Island, Malaysia - Md. Rosli, Nur Suhaila; Ahmad, Zuhairi; Azman, Nur Syahira Azlyn; Mustapa, Mohd Zaini (IIUM, 2019)
of the spatially distributed data needed for ArcSWAT interface. The main objective of soil data definition is to create a soil database for hydrologic response unit (HRU) analysis in SWAT model. Soil data definition includes Langkawi geological map, soil type, soil texture and soil S5id code. Geological formation of soil in Langkawi consist of alluvium, granite, Machincang, Setul, Chuping and Singa formation. The dominant soil group is Acrisols (soil unit name: Orthic Acrisols, Ao) and the dominant soil texture classification is sandy clay loam. MY4282 and MY4464 are the soil S5id code for soil classification table. Forest (FRSE), has the highest land use area within Langkawi Is- land watershed; 13202 ha with percentage of 75.59%. The lowest of land use area is industrial (UIDU), 105.44 ha (0.60%). MY4464 has the highest percentage of coverage (100%; 995.52 ha) within the urban (URBN) area. Industrial (UIDU) area recorded the highest percentage of coverage for MY4284 (100%; 105.44 ha). This soil database has been successfully tested as a fully functional database for the SWAT model analysis.